Valkoinen kulta lasten liikuttajana : hiihto-opetus suomalaisissa peruskouluissa - Pulkkanen, Iida (2024)
The main purpose of this Master´s Thesis is to study the position of the Finnish national sport, cross-country skiing in the Finnish education system, especially in primary education. The goal of this survey is to clarify how much cross-country skiing does physical education contain and what factors are affecting the count. As well as the target is to sort out what subject matters does the cross-country skiing lessons involve and do they geographically vary. The third point is to understand what are the goals that teachers try to reach with teaching cross-country skiing. The target group is the physical education teachers teaching in Finland, the members of the association of Finnish physical education teachers, to be exact (N=1335). The number of answers was 142. Locomotion in nature, especially on the snow has been a lifeline in the history of the northern people. Cross-country skiing has a significant history in the everyday life as well as in the Finnish wars and as an influencer of the public health. About a hundred years ago the Finns faced a unique enthusiasm for cross-country skiing as literally everyone was skiing up here. This phenomenon brought cross-country skiing into the Finnish education system, to schools. Only by understanding the nowadays it is possible to affect the future, sustainably. The research material was collected with an electric questionnaire and the material was analysed with quantitative research methods, such as SPSS-program. The main analysis methods are crosstabulation, Pearson correlation coefficient and one-way ANOVA. The survey shows that cross-country skiing yet actively is a part of the Finnish physical education in primary school. There is a correlation between the geographical location of the school and the amount of cross-country skiing lessons. However, the teachers´ age does not have a statistically significant correlation. The amount of cross-country skiing is positively affected by the location of the ski trail and the self-experienced professional competence to teaching the sport. The most negative effects are the condition of the equipment and the students´ desires for the contents of physical education. The cross-country skiing lessons involve the basic skills of movement with skis as well as playing games. However, the main subject matters are ski runs alone and technique practice. With time, the goals for teaching Nordic teaching have modified to more individually rather than socially serving. The clearance of this topic is current, because of the critical years and decades the sport is living, not least because of the climate and other resources. The culture of cross-country skiing must be consciously protected in order to maintain its position and value as a serious winter sport. Fitness skiing is living its golden years, whilst the number of competitive skiers is consistently decreasing. By paying attention to the teaching of cross-country skiing in schools we may increase the number of skiers in ski clubs as well. There is no such scientific research handling cross-country skiing, especially in school context. This is why it may be a good timing to have a look to the skis in school.